CBT Approach in Handling the Phenomenon of “The Death of Expertise” - Naily Nur Rochmah; Asna (Journal of Islamic Communication and Counseling, 2025)
This study aims to explore the potential of cognitive behavioral therapy (CBT) approach in dealing with the phenomenon of "the death of expertise" among teenagers. The research method used is qualitative with a case study approach, through focus group discussions (FGD), interviews, and observations of students at MAN 3 Jember and SMA 1 Negeri Kencong. The results showed that the decline in trust in experts was influenced by social media algorithms and biased information consumption patterns. CBT helps shape critical thinking and fosters respect for expertise. This study contributes to the application of CBT in educational settings as an intervention against digital cognitive biases, bridging psychology and media literacy approaches, in addition to expanding the use of CBT from the clinical to the educational domain, and offering a new strategy to improve critical thinking and respect for scientific authority among adolescents. In conclusion, CBT is a relevant intervention that has the potential to address the challenge of digital information bias towards scientific authority.